Talent show scaredy-pants - Klein, Abby (Klein, Abby. Ready, Freddy!, 2005)
Freddy is nervous about the first-grade Grandparent's Day talent show, especially with Max bullying and teasing him, but Freddy's dad has an idea that might make Freddy a star and get Max to back off, too.